Visible light mediated desilylative C(sp(2))-C(sp(2)) cross-coupling reactions of arylsilanes with aryldiazonium salts under Au(i)/Au(iii) catalysis - Chakrabarty, Indradweep; Akram, Manjur O.; Biswas, Suprakash; Patil, Nitin T. (Chemical Communications, 2018)
Desilylative C(sp(2))-C(sp(2)) cross-coupling reactions of arylsilanes with aryldiazonium salts under Au(i)/photoredox catalysis have been reported. The addition of Cu-salts as catalysts was found to be crucial for the success of this transformation.